PEMANFAATAN LIMBAH NON B3 FLY ASH DAN BOTTOM ASH DARI KEGIATAN PLTU SEBAGAI SUBTITUSI BAHAN BAKU PEMBUATAN PAVING BLOCK DAN BATAKO - Erzha, Nutfahryza; Sitorus, Saibun; Panggabean, Aman Sentosa (Jurusan Kimia FMIPA UNMUL, 2024)
The use of coal in power plant activities will produce solid waste in the form of fly ash and bottom ash. Alternative management to reduce the volume of ash waste is through utilization. Therefore, this study aims to determine the toxic characteristics of bottom ash fly ash waste, determine the physical properties of the compressive strength of paving blocks and bricks from the substitution of fly ash and bottom ash, as well as the most optimal proportion of substitution of the product based on the compressive strength parameter. Compatibility of Toxic Waste Characteristics is carried out through the Toxicity Characteristic Leaching Procedure (TCLP) test. Variation of optimal substitution for compressive strength is known through variations of fly ash and bottom ash substitution, for brick products which are 5%, 10%, 15%, and 20%, and for paving blocks which are 10%, 20%, 30%, and 40%. Through the TCLP test, it is known that the waste is below the TCLP A and TCLP B quality standards so it can be categorized as non toxic and hazardous waste. The results of using fly ash and bottom ash in brick products meet the requirements for compressive strength according to SNI 03-0349-1989. The results of using fly ash and bottom ash in paving block products meet the requirements for compressive strength according to SNI 03-0691-1996. The optimal variation of fly ash substitution for bricks is with 5% fly ash substitution that produces a compressive strength value of 201.42 kg/cm2 and paving blocks with 10% fly ash substitution that produces a compressive strength value of 225.01 kg/cm2. The optimal variation of bottom ash substitution for brick is with 5% bottom ash substitution that produces a compressive strength value of 226.30 kg/cm2 and for paving block is with 10% bottom ash substitution that produces a compressive strength value of 308.22 kg/cm2.